Empirical Research and Normative Theory Transdisciplinary Perspectives on Two Methodical Traditions Between Separation and Interdependence - Bauer, Alexander Max; Meyerhuber, Malte (De Gruyter, 2020)
Two questions often shape our view of the world. On the one hand, we ask what there is, on the other hand, we ask what there ought to be. Empirical research and normative theory, the methodological traditions concerned with these questions, entered a difficult relationship, from at least as early as around the time of the advent of modern sciences. To this day, there remains a strong separation between the two domains, with both tending to neglect discourses and results from the other. Contrary to a verdict of strict segregation between "is" and "ought," there are, nowadays, various attempts to integrate both theoretical approaches. This calls for a discourse on the relation between empirical research and normative theory. In this volume, scholars from different disciplines - including psychology, sociology, economics, and philosophy - discuss the possible desired or undesired influences on, and limits of, the integration of these two approaches.